The Effect Of Nesting On The Behavior Of Low Birth Weight Babies At Medi Medika Clinic, Tangerang Regency Year 2022 - Nikhla Arvina; Maryati Sutarno (International Journal of Health and Pharmaceutical (IJHP), 2023)
Low birth weight babies (LBW) are babies with a birth weight of less than 2500 grams regardless of gestational age. Birth weight is the weight of a baby who is weighed within 1 (one) hour after birth (Amin & Hardhi, 2016). LBW can occur because the gestational age is less than normal, namely 37 weeks and the baby's weight is lower than babies in general (Ministry of Health, 2018). To determine the effect of nesting on the behavior of low birth weight newborns at the Medi Medika Clinic, Tangerang Regency. Using quai experimental design with one group pretest posttest involving one group of subjects. The research sample was 30 low birth weight newborns who were treated at the Medi Medika Clinic in Tangerang Regency and were selected by purposive sampling technique. Research data were analyzed using paired t-test and Wilcoxon test. The results of the analysis showed that there was a significant effect of the use of nesting on the behavior of low birth weight newborns (p = 0.000). The use of nesting as a form of developmental care can facilitate the achievement of better rest (which is characterized by the regularity of physiological functions and the achievement of quiet sleep behavior), so it needs to be implemented in the care of low birth weight newborns at the Medi Medika Clinic, Tangerang Regency. There is a significant effect of the use of nesting on the behavior of low birth weight newborns. Pregnant women are advised to seek more information regarding pregnancy care through health workers, especially midwives, posyandu officers, the mass media and others, so they can recognize the low risk of newborns.